(untitled) (Academia Science Repository, 2023)
Various approaches to the study of the main problems of family education are considered; the results of the study of the influence of parental attitudes on the formation of attitudes towards the child are presented. It contains an analysis of the results of testing families with children aged 5 to 16 years and generalized conclusions